2014
DOI: 10.1371/journal.pone.0106677
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Affects the Biopsy-Mediated Detection of Prostate Cancer, Particularly High-Grade Prostate Cancer: A Dose-Response Meta-Analysis of 29,464 Patients

Abstract: Background and ObjectivesIn previous studies, obesity (measured according to the body mass index) has correlated inconsistently with the risk of biopsy-measured prostate cancer, and specifically high-grade prostate cancer. This meta-analysis aimed to clarify these correlations.MethodsA comprehensive literature search of the MEDLINE and EMBASE databases was conducted for relevant studies published through January 2014. The pooled estimates of odds ratios (OR) and confidence intervals (CI) were computed, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 38 publications
0
38
0
3
Order By: Relevance
“…Similar relationships have been observed for PCa, although the findings are inconsistent; some studies report an association between obesity and increased PCa incidence , whilst others have shown no or only modest associations with PCa incidence . Meta‐analyses designed to examine robustly the association between obesity and PCa incidence are equally inconclusive .…”
Section: Obesity and Prostate Cancermentioning
confidence: 77%
See 1 more Smart Citation
“…Similar relationships have been observed for PCa, although the findings are inconsistent; some studies report an association between obesity and increased PCa incidence , whilst others have shown no or only modest associations with PCa incidence . Meta‐analyses designed to examine robustly the association between obesity and PCa incidence are equally inconclusive .…”
Section: Obesity and Prostate Cancermentioning
confidence: 77%
“…This increase in PCa incidence has largely mirrored the increase in the prevalence of obesity and metabolic syndrome . While there are conflicting reports on the effect of obesity on PCa incidence , there is an increasing body of evidence demonstrating associations between obesity and more aggressive carcinoma, poor treatment outcome and higher risk of cancer‐specific mortality for PCa . A range of mechanisms have been proposed to underpin the effects of an obese environment on PCa behaviour, including increased systemic inflammation, hyperinsulinaemia, altered adipokine profiles and increased lipid availability .…”
Section: Introductionmentioning
confidence: 99%
“…Obesity may be salient to racial disparities in prostate cancer given that it is influenced by environmental and genetic factors, 7 is more prevalent among African Americans, 8,9 affects physiologic processes associated with cancer etiology, 10,11 and may affect the sensitivity of prostate-specific antigen (PSA) screening. 12,13 …”
mentioning
confidence: 99%
“…Although individual studies are conflicted regarding the association between obesity and prostate cancer risk, a number of large meta-analyses have reported that obesity is associated with a modestly elevated total prostate cancer incidence (Bergstrom, et al 2001; Hu, et al 2014; MacInnis and English 2006; Renehan, et al 2008). One meta-analysis demonstrated that findings from the individual contributing studies differed by geographic region (Renehan et al 2008), thereby offering insight into these somewhat conflicted results.…”
Section: Transdisciplinary Insights Into Associations Between Obesmentioning
confidence: 99%